Web-based Queue Machine Development using Raspberry and ESP8266 - Anggit Damaz Istoko; Aulia Faqih Rifa'i (Faculty of Science and Technology, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2018)
At a recent time, a computer-based queue machine, which is using the computer as both a client and a server, is rated to be less practical and inefficient. In this case, the queue machine will need a number of the computer as many as the locket and the network configuration. Given these points, the aim of this research is to build a practice and applicable queue machine. In the development of this system, the writer adopted the prototyping method. Acquiring Arduino Uno to convert the analog signal become a digital which will be shown in the LED P10, utilizing NodeMCU ESP8266 as a WiFi module, and adapting Raspberry Pi 3 as a server, this queue system expected to solve the problem before. In addition, to build the web, this queue system is using javascript and node.js as the software. This research derives a practice, easy to use, and portable queue machine because it uses wifi for their connection.